The Invisibility of Privilege: A critique of intersectional models of identity - Carastathis, Anna (Les ateliers de l'éthique / The Ethics Forum, 2008)
In this paper, I argue that intersectionality, the prevailing way of conceptualizing the relation between axes or systems of oppression (race, class, gender), illicitly imports the very model it purports to overcome: that is, the unitary model of identity. I first define “intersectionality” and distinguish between three senses that are frequently conflated. Then I subject the model to an analytic critique, revealing its hidden presuppositions about identity. Finally, I suggest that solidarity serves as a better norm for feminist practice than inclusion of “difference,” which seems to be the norm underlying many intersectional accounts.